2007
DOI: 10.1038/sj.ijir.3901605
|View full text |Cite
|
Sign up to set email alerts
|

Is the metabolic syndrome a risk factor for female sexual dysfunction in sexually active women?

Abstract: Despite of the high prevalence, pathogenesis of female sexual dysfunction (FSD) is still poorly understood. A consecutive series of sexually active women underwent a health investigation and completed a questionnaire on FSD. Metabolic syndrome (MS) was defined according to the International Diabetes Federation definition. A total of 538 women with a mean age of 44 years (range: 30-69) was analysed. The premenopausal group comprised 329 women (61.2%) with a mean age of 38.5 years; the postmenopausal cohort cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 20 publications
6
64
3
4
Order By: Relevance
“…29,30 Somatic comorbidity was entered into our multivariate analysis but showed no significant association with low PISQ-12 scores. We recognize that assessing the impact of comorbidity on lower urinary tract and sexual function may require sophisticated tools, developed and validated specifically for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Somatic comorbidity was entered into our multivariate analysis but showed no significant association with low PISQ-12 scores. We recognize that assessing the impact of comorbidity on lower urinary tract and sexual function may require sophisticated tools, developed and validated specifically for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Study on postmenopausal women in Austria showed that the prevalence of metabolic syndrome was 32.6% [26]. In another study on postmenopausal women in Chengdu, China, the prevalence of metabolic syndrome was shown to be 37.34% [25].…”
Section: Different Viewsmentioning
confidence: 96%
“…Studies indicated that women aged more than 55 have a higher incidence of cardiovascular disease than younger women [8,[22][23]. Other studies showed that there is a high prevalence of metabolic syndrome among postmenopausal women, which varies from 32.6% to 41.5 % [24][25][26]. Study of Rossi et al [27] demonstrated that postmenopausal women with metabolic syndrome have lower incidence of cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Los factores asociados a la disfunción sexual han sido estudiados por varios autores, registrando el síndrome metabólico como un factor de riesgo independiente (16)(17)(18), la edad, el grado de instrucción, la salud física (19,20) y mental en la mujer (21), aunque otros autores refieren además el estado civil casado, hábito de fumar (22), así como tener más de 14 años de matrimonio, más de 2 hijos, el grado de instrucción, el tener una pareja mayor de 42 años (23) y el uso de terapia antidepresiva (24).…”
Section: Introductionunclassified
“…Results: 342 women (114 cases / 228 controls) participated, with a mean age of 40.5 ± 9.2 and a BMI of 25.2 ± 3.5; 45.9% (157) are married; 53.5% (183) with secondary level, 41.5% (142) housewives, 17.8% (61) menopausal, 34.8% (119) with metabolic syndrome. In addition, with chronic disease, 32.7% (112), anxiety 16.4% (56), depression 5% (17), drug consumption 35.1% (72). In the bivariate analysis, the factors of widowhood, retired occupation, 2 previous pregnancies, ill health, chronic illness, smoking, anxiety and depression, and as a protective factor, married marital status and higher educational level as associated factors.…”
mentioning
confidence: 99%